Penile dimensions and men's perceptions of condom fit and feel. Issue 2 (11th December 2008) - Reece, M; Herbenick, D; Dodge, B
Abstract : Objectives: Sexual health professionals continue to promote correct and consistent condom use among sexually active individuals yet research indicates that some men remain resistant to using condoms because of perceptions that they do not fit properly or feel comfortable. This study empirically assessed relations between men's penile dimensions and their perceptions of condom fit and feel. Methods: Data related to demographics, a bivariate calculation of erect penile length and circumference, and perceptions of condom fit and feel were analysed from 1661 adult men from 50 US states Results: While many men reported that condoms generally fit fine and feel comfortable, at clearly identifiable intersections of length and circumference relations between penile dimensions and perceptions of condom fit and feel existed, particularly for those men who felt that condoms were "too long" (p<0.004), "too short" (p<0.001), "too loose" (p<0.047) or "too tight" (p<0.001). Conclusions: These analyses provide empirical insights into the relations between bivariate penile dimensions (the intersection of length and circumference) and men's perceptions of the positive and negative aspects of condom fit and feel. Those men with the most negative perceptions of condom fit and feel may benefit from an assessment of their condom-related concerns as a component of community and clinic based STI prevention interventions in order to help them select from the variety of condoms in the marketplace that they may find to be better fitting or more comfortable.